Percobaan Pendahuluan Pengaruh Minyak Mimba dan Ekstrak Biji Srikaya terhadap Mortalitas Helopeltis sp. (Heteroptera: Miridae) - Soekadar Wiryadiputra (Jurnal Perlindungan Tanaman Indonesia, 1998)
Preliminary trial of neem (Azadirachta indica A. Juss.) seed oil and aqueous seed extract of custard-apple (Annona squamosa L.) on the mortality of Helopeltis sp. has been conducted in laboratory condition. Neem oil obtained from directly pressed seed kernel and aqueous extract of custard-apple seed at concentration of 1.0% and 2.0% were significantly causing the mortality of the insect. The effectiveness of the substances in killing Helopeltis were not significantly different with propoxur and sipermethrin insecticides. Neem oil obtained from steamed seed before being pressed and aqueous leaf extracts were also causing high mortality but still lower than two substances previously applied. Number of eggs produced by Helopeltis treated with the neem oil and seed extract of custard-apple were also significantly lower than control.